2005
DOI: 10.1634/stemcells.2004-0264
|View full text |Cite
|
Sign up to set email alerts
|

Cell Renewing in Neuroblastoma: Electrophysiological and Immunocytochemical Characterization of Stem Cells and Derivatives

Abstract: We explored the stem cell compartment of the SH-SY5Y neuroblastoma (NB) clone and its development by a novel approach, integrating clonal and immunocytochemical investigations with patch-clamp measurements of ion currents simultaneously expressed on single cells. The currents selected were the triad I HERG , I KDR , I Na , normally expressed at varying mutual ratios during development of neural crest stem cells, from which NB derives upon neoplastic transformation. These ratios could be used as electrophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 47 publications
2
44
0
1
Order By: Relevance
“…The human neuroblastoma SY5Y clone and its derivatives were maintained in RPMI 1640 and cultured as previously reported (2).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The human neuroblastoma SY5Y clone and its derivatives were maintained in RPMI 1640 and cultured as previously reported (2).…”
Section: Methodsmentioning
confidence: 99%
“…We carried out a program of research aimed at revealing the process of cell renewing in neuroblastoma, a tumor of childhood characterized by an unpredictable clinical course and a remarkable plasticity, resulting in multiform phenotypes (1,2). A peculiar feature of this tumor is the tendency to regress from a malignant to a benign phenotype (ganglioneuroma or, rarely, a neurofibromatous mass; ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ion channels are widely expressed in proliferative cells which can modulate the proliferation of cells by affecting the cell cycle (MacFarlane & Sontheimer, 2000;Ouadid-Ahidouch et al, 2004;Biagiotti et al, 2006). Recent studies from our group and others have demonstrated that multifunctional ion channels are heterogeneously expressed in various species of MSCs (Li et al, 2005;Deng et al, 2006;Li et al, 2006;Park et al, 2007;Tao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%